Amorphous molybdenum disulfide nanocomposite material and preparation method and application thereof

By inserting DT molecules into the MoS2 layer and using CNTs as scaffolds, amorphous a-MoS2/DT@CNTs composites were prepared, which solved the problems of low conductivity and poor reversibility caused by the large block structure of MoS2, and achieved excellent rate performance and long cycle stability.

CN118579839BActive Publication Date: 2025-04-18LIAONING UNIVERSITY OF PETROLEUM AND CHEMICAL TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410806459.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-20
Publication Date
2025-04-18
Estimated Expiration
2044-06-20

AI Technical Summary

Technical Problem

The existing sodium ion battery negative electrode material MoS2 has low conductivity and mismatched Na+ diffusion rate due to its large block structure, resulting in problems of volume expansion, agglomeration and poor reversibility, which affects capacity and cycling stability.

Method used

Amorphous molybdenum disulfide nanocomposite a-MoS2/DT@CNTs were used to insert disodium terephthalate (DT) molecules into the MoS2 layer and use carbon nanotubes (CNTs) as a scaffold to expand the layer spacing, enhance the layer structure, and improve the dynamic performance of the material.

Benefits of technology

It achieves excellent rate performance and long cycle stability, reduces interlayer force, improves the diffusion and transmission of electrolyte ions, and improves the electrochemical performance and structural stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118579839B_ABST
    Figure CN118579839B_ABST
Patent Text Reader

Abstract

The invention discloses an amorphous molybdenum disulfide nanocomposite material and a preparation method and application thereof, belonging to the field of negative electrode materials for ion batteries. The amorphous molybdenum disulfide nanocomposite material provided is (NH4)6Mo7O 24 ·4H2O and C2H5NS are molybdenum disulfide precursors, DT (C8H4Na2O4) is an intercalation agent, and CNTs is a supporting skeleton, which is obtained by a microwave hydrothermal reaction at a reaction temperature of 180°C for 2.5 hours. With the expansion of interlayer spacing, the enhancement of layer structure and the role of amorphous MoS2, the composite material a‑MoS2 / DT@CNTs has achieved excellent rate performance and long cycle stability. Raman and EIS further prove that the composite material a‑MoS2 / DT@CNTs has an organic-inorganic synergistic effect, and has a small interlayer force and excellent diffusion kinetics during the charge and discharge process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of negative electrode materials for ion batteries, and specifically relates to an amorphous molybdenum disulfide nanocomposite material and a preparation method and application thereof. Background Art

[0002] Advanced energy storage technologies are key to managing future energy supply and demand from sustainable and renewable sources. Lithium-ion batteries (LIBs) have played an important role in energy storage due to their high energy density, long life, and low environmental impact. Scarce lithium resources can no longer meet the growing demand. Sodium-ion batteries have attracted great attention due to their high abundance (the fourth most abundant element in the earth's crust), low cost, and suitable electrochemical voltage (-2.71V vs. SHE). However, sodium has a large ionic radius. This results in graphite with an interlayer spacing of only 0.34 nm being insufficient to support the rapid and reversible insertion and extraction of sodium ions. Therefore, the development of suitable negative electrode materials has become a key challenge for the commercialization of sodium-ion batteries.

[0003] Among many negative electrode materials, MoS2 is a typical two-dimensional transition metal sulfide (TMCs) with an interlayer spacing of 0.62nm and weak van der Waals forces between layers. This unique structure can lead to Na + Rapid insertion and extraction, and provides high capacity (theoretical specific capacity is 669mAh g -1 ), is considered to be an ideal candidate for anode materials for sodium-ion batteries. However, bulk MoS2 has low electrical conductivity and is comparable to Na + The mismatch in diffusion rate causes problems such as volume expansion, agglomeration and poor reversibility when used as a negative electrode material, resulting in poor capacity and cycle stability. The construction of nanostructures such as nanoflowers, nanospheres, and nanorods can effectively alleviate the problems of volume expansion and agglomeration, increase the active sites of electrode materials, and increase the contact area with the electrolyte, thereby improving the cycle performance and rate performance of MoS2. However, the poor kinetics of nano-MoS2-based storage materials is caused by the incompatibility of a large number of inserted ions with the steric hindrance lattice space in the host material. The strategy of inserting guest molecules into the MoS2 layer can effectively increase the lattice spacing and reduce the steric hindrance. Summary of the invention

[0004] The purpose of the present invention is to provide an amorphous molybdenum disulfide nanocomposite material and a preparation method and application thereof. The composite material has excellent rate performance and long cycle stability. When applied to a negative electrode material of a sodium battery, it has a small interlayer force and excellent diffusion kinetics during the charge and discharge process. The preparation method is simple and easy to operate.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing an amorphous molybdenum disulfide nanocomposite material comprises the following steps:

[0007] S1. Add CNTs into deionized water and stir to obtain a CNTs solution;

[0008] S2. Add (NH4)6Mo7O to the CNTs solution in S1. 24 4H2O, C2H5NS and C8H4Na2O4, stir for 10-50min to form a mixed solution;

[0009] S3, transferring the mixed solution in S2 to a 100 mL polytetrafluoroethylene-lined autoclave for reaction to obtain a black product;

[0010] S4, collecting the black product described in S3, and washing it three times with deionized water and anhydrous ethanol respectively;

[0011] S5. The washed black product is placed in an oven for drying to obtain an a-MoS2 / DT@CNTs composite material.

[0012] Preferably, the CNTs in S1 are one or two of graphene, single-walled carbon nanotubes, and double-walled carbon nanotubes.

[0013] Preferably, the stirring time in S1 is 10-50 min.

[0014] Preferably, the stirring time in S1 is 20 min.

[0015] Preferably, (NH4)6Mo7O in S2 24 The molar ratio of 4H2O, C2H5NS and C8H4Na2O4 is 1:1:0.05-1:20:0.5.

[0016] Preferably, (NH4)6Mo7O in S2 24 The molar ratio of 4H2O, C2H5NS and C8H4Na2O4 is 1:2:0.2

[0017] Preferably, the reaction temperature in S3 is 90-240° C., and the reaction time is 0.5-5 h.

[0018] Preferably, the reaction temperature in S3 is 150° C., and the reaction time is 2 h.

[0019] Preferably, in S5, the washed black product is placed in an oven at 60-80° C. and dried for 12-24 hours.

[0020] Preferably, in S5, the washed black product is placed in an oven at 60° C. and dried for 12 hours.

[0021] The invention also provides an amorphous molybdenum disulfide nanocomposite material prepared by the preparation method.

[0022] The present invention also provides an amorphous molybdenum disulfide nanocomposite material prepared by the preparation method or a method for preparing MoS x Application in sodium battery negative electrode materials.

[0023] The present invention also provides a method for MoS x A negative electrode material for a sodium battery, comprising the above-mentioned amorphous molybdenum disulfide nanocomposite material.

[0024] The present invention uses organic reagents as supporting materials in the layer and carbon nanotubes as the skeleton, and uses disodium terephthalate (Na2C8H4O4, DT), a conjugated carboxylic acid organic molecule with carbon-oxygen double bonds (C=O) with sodium storage capacity, as a molecular template to synthesize an amorphous a-MoS2 / DT@CNTs material with an extended layer. The DT molecule not only plays a supporting role, but also realizes the coordinated sodium storage of organic-inorganic materials. In addition, amorphous materials can maintain a higher probability of electrical contact between transition metal particles. The preparation of amorphous a-MoS2 / DT@CNTs can further improve the diffusion performance and reversibility of electrode materials, and achieve high-rate cycle stability under the action of the CNTs skeleton.

[0025] Compared with the prior art, the present invention has the following advantages and technical effects:

[0026] (1) The present invention provides an amorphous molybdenum disulfide nanocomposite material and a preparation method and application thereof. The preparation method of the present invention is based on (NH4)6Mo7O 24 ·4H2O and C2H5NS are molybdenum disulfide precursors, DT is an intercalation reagent, and CNTs are a supporting skeleton. A microwave hydrothermal reaction is carried out at a reaction temperature of 180°C for 2.5 hours to obtain a-MoS2 / DT@CNTs composite material. This preparation method only uses a one-step microwave hydrothermal method and is simple and easy to operate.

[0027] (2) The a-MoS2 / DT@CNTs composite material provided by the present invention achieves excellent rate performance and long cycle stability by expanding the interlayer spacing, strengthening the layer structure and the effect of amorphous MoS2. The expansion of the interlayer spacing of the composite material helps the diffusion and transmission of electrolyte ions, thereby improving the electrochemical performance of the material. At the same time, the layered structure of the composite material is significantly enhanced, which helps to improve the structural stability and mechanical strength of the material.

[0028] (3) Raman and electrochemical impedance spectroscopy (EIS) tests further demonstrated the synergistic effect of organic-inorganic components in a-MoS2 / DT@CNTs. This synergistic effect enhances the overall performance of the material. When it is used as a negative electrode material, the composite material exhibits a smaller interlayer force during the charge and discharge process, which helps to reduce polarization and improve the charge and discharge efficiency. The a-MoS2 / DT@CNTs amorphous molybdenum disulfide nanocomposite material of the present invention shows great application potential and performance advantages in the field of electrochemical energy storage, especially in the negative electrode materials of lithium-ion batteries.

[0029] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a microscopic morphology of the composite material provided by Example 1, Comparative Example 1 and Comparative Example 2 of the present invention, wherein: Figure 1 a in the figure is the SEM image of a-MoS2 / DT@CNTs provided in Example 1, with a scale of 500 nm. Figure 1 b is a TEM image of a-MoS2 / DT@CNTs at a scale of 100 nm provided in Example 1, with a scale of 100 nm. Figure 1 c in the figure is the HR-TEM image of a-MoS2 provided in Comparative Example 1, with a scale of 5 nm. Figure 1 d in the figure is the SAED image of MoS2 / DT@CNTs provided in Comparative Example 3. Figure 1 e in the figure is the SEM element distribution of a-MoS2 / DT@CNTs provided in Example 1, with a scale of 500 nm. Figure 1 f is the Mo element distribution SEM image of a-MoS2 / DT@CNTs provided in Example 1, with a scale of 500 nm. Figure 1 g in the figure is the SEM image of the S element distribution of a-MoS2 / DT@CNTs provided in Example 1, with a scale of 500 nm. Figure 1 h in the figure is the SEM image of the C element distribution of a-MoS2 / DT@CNTs provided in Example 1, with a scale of 500 nm;

[0031] Figure 2 is a comparison result of the properties of the composite material provided by Example 1 of the present invention and Comparative Example 1, wherein: Figure 2 a in the figure is a comparison diagram of XRD of the composite materials of Example 1 and Comparative Example 1, Figure 2 b is a comparison of the Raman spectra of the composite materials of Example 1 and Comparative Example 1, Figure 2 c is a comparison chart of FT-IR spectra of the composite materials of Example 1 and Comparative Example 1, Figure 2 d in is a comparison diagram of the TGA spectra of the composite materials of Example 1 and Comparative Example 1;

[0032] Figure 3 is the XPS spectrum of the composite material provided in Example 1 and Comparative Example 1 of the present invention, wherein: Figure 3 a in the figure is the Mo 3d XPS spectrum of the composite material of Example 1, Figure 3 b in the figure is the S2p XPS spectrum of the composite material of Example 1, Figure 3 c in the figure is the Mo 3d XPS spectrum of the composite material of Comparative Example 1, Figure 3 d in is the S2p XPS spectrum of the composite material of Comparative Example 1;

[0033] Figure 4 The diffraction pattern of the MoS2 / DT@CNTs composite material provided for Comparative Example 2. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0035] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0036] Example 1

[0037] This embodiment provides a method for preparing an amorphous molybdenum disulfide nanocomposite material, comprising the following steps:

[0038] S1. Add 30 mg of CNTs (single-arm carbon tubes) into 20 mL of deionized water and stir for 30 min to obtain a CNTs solution;

[0039] S2. Add (NH4)6Mo7O to the CNTs solution 24 4H2O (0.5mmol, 618mg), C2H5NS (7mmol, 526mg) and C8H4Na2O4 (0.05mmol, 10.5mg) were stirred for 30min to form a mixed solution;

[0040] S3, transferring the mixed solution to a 100 mL polytetrafluoroethylene-lined autoclave, and reacting at 180° C. for 2.5 h;

[0041] S4, collecting the black product after the reaction in S3, and washing it three times with deionized water and anhydrous ethanol respectively;

[0042] S5. The washed black product was placed in an oven at 60°C and dried for 12 h to obtain an a-MoS2 / DT@CNTs composite material.

[0043] Comparative Example 1

[0044] This embodiment provides a method for preparing an a-MoS2 composite material. The preparation method is the same as that of Example 1, except that no CNTs are added to S1 and no C8H4Na2O4 (DT) is added to S2.

[0045] Comparative Example 2

[0046] This embodiment provides a method for preparing a MoS2 / DT@CNTs composite material. The a-MoS2 / DT@CNTs composite material prepared in Example 1 is heated in a tubular furnace under an argon atmosphere at 5°C min -1 The temperature was raised to 500 °C and maintained at this temperature for 2 h to allow a-MoS2 / DT@CNTs to crystallize into MoS2 / DT@CNTs.

[0047] The effects of the composite materials provided in the above embodiments were verified by the following tests:

[0048] Physicochemical characterization:

[0049] The phase structure and composition of the samples were studied by X-ray polycrystalline powder diffractometer (XRD, D8 Advance, Germany) (CuKa, l = 0.154056nm). The morphology and size were analyzed by field emission electron scanning microscopy (SEM, SU8010, Japan) and high-resolution transmission electron microscopy (TEM, JEM-2100F, Japan). X-ray photoelectron spectroscopy (XPS, ESCALAB Xi + , Thermo Fisher Scientific) was used to detect the chemical state of the elements. Thermogravimetric analysis was performed using a thermogravimetric-differential thermal analyzer (TGA, Q600, Amercia) in air at a heating rate of 10 °C min -1, the temperature was up to 600 ° C. Raman spectra were obtained under 532 nm laser excitation (Raman, DXR, Thermo Fisher). FT-IR spectra were tested on an infrared spectrometer (FIR, FTIR-660+610, Agilent) to check the chemical bonds and verify the presence of organic matter.

[0050] The test results are as follows:

[0051] Figure 1 The microscopic morphology of the composite material provided in the above embodiment. Figure 1 From the a in the figure, it can be seen that the a-MoS2 / DT@CNTs composite material provided in Example 1 mainly has a nanosphere structure, and the doped CNTs cross the nanospheres, supporting the crushing of the nanosheets, thereby improving the stability of the material structure. Figure 1 Figure b is a TEM image of the a-MoS2 / DT@CNTs composite material provided in Example 1 at a scale of 100 nm, which clearly shows that the diameter of the nanospheres of a-MoS2 / DT@CNTs is about 500 nm and is composed of multiple layers of folded nanosheets.

[0052] By observation Figure 1 In Figure c, i.e., the HR-TEM image of the a-MoS2 composite material provided in Comparative Example 1, it can be observed that the lattice spacing of a-MoS2 is widened to 0.723 nm, corresponding to the (002) crystal plane of the a-MoS2 crystal. Figure 1 d, that is, compared with the MoS2 / DT@CNTs provided in Comparative Example 2, the crystal traces of a-MoS2 / DT@CNTs are not obvious, and mainly manifest as multi-ring diffraction spots. These conclusions show that the crystallinity of the a-MoS2 / DT@CNTs composite material provided in Example 1 is relatively low. In addition, Figure 1 It can be seen from eh that the X-ray element mapping diagram of the a-MoS2 / DT@CNTs composite material provided in Example 1 shows that the three elements Mo, S and C are evenly distributed in the structure.

[0053] The crystal structures of the a-MoS2 composite material in Comparative Example 1 and the a-MoS2 / DT@CNTs composite material in Example 1 were studied by XRD. Figure 2 a and Figure 4It can be seen that compared with MoS2 / DT@CNTs in Comparative Example 2, the (002) diffraction peak of a-MoS2 / DT@CNTs in Example 1 is not obvious, indicating that its crystallinity is low. It is also observed that the (002) diffraction peak of a-MoS2 / DT@CNTs in Example 1 is slightly left-shifted compared with a-MoS2 in Comparative Example 1, which indicates that its interlayer spacing has been expanded. According to the Bragg equation, after the insertion of DT molecules, the d spacing is expanded to and Figure 1 The HR-TEM results in c are similar. Figure 2 c, FT-IR spectrum also confirmed the existence of DT. Figure 2 As shown in b, it is located at 3452cm -1 The absorption band at 1639cm is the stretching vibration peak of H2O, indicating that the synthesized sample contains a small amount of crystal water. -1 、1400cm -1 The peak at 1208 cm is attributed to the C=C stretching vibration peak of the aromatic ring, while the peak at 1208 cm -1 The stretching vibration peaks of CH indicate that DT is successfully embedded in MoS2 molecules. -1 In the wavelength range, the Mo-Mo peak of a-MoS2 / DT@CNTs provided in Example 1 has a significant blue shift compared to a-MoS2 provided in Comparative Example 1, indicating that there is an organic-inorganic synergistic effect between DT and MoS2, which enables DT to exist stably in the middle of the layer. Figure 2 As can be seen from the figure d, a-MoS x / DT@CNTs have four descending platforms, which is better than a-MoS x There are two more platforms, which are the combustion and decomposition reactions of DT and CNTs. x / DT@CNTs and a-MoS x The first weight loss before 180℃ is mainly related to the crystallization water and absorbed water of the sample; the second step is the weight loss of the sample between 180℃ and 330℃, which is attributed to the combustion and decomposition reaction of CNTs and oxygen in the sample; the third step is the weight loss between 330℃ and 420℃, which is due to the decomposition of MoS x The fourth step is the weight loss of the sample between 420℃-540℃, which is attributed to the combustion decomposition reaction of DTs in the sample. The total mass contents of CNTs and DT are calculated to be 6.88% and 5.32%, respectively. TGA test further proves that DT and CNTs are successfully embedded in MoS x In the molecule.

[0054] The element valence and composition information of the composite materials provided in Example 1 and Comparative Example 1 were analyzed by X-ray photoelectron spectroscopy (XPS). The XPS overall spectrum (SI) showed that the a-MoS2 / DT@CNTs composite nanomaterial mainly contained four elements: Mo, S, O, and C. Figure 3 From a in Fig. 1, we can see that the XPS spectrum of Mo 3d has two obvious peaks at 232.17 and 229.03 eV, which correspond to the characteristic peaks of Mo 3d3 / 2 and Mo 3d5 / 2 of Mo(IV), respectively. However, in addition to this, Mo 3d has two weak peaks, which are the characteristic peaks of Mo 3d3 / 2 (233.35 eV) and Mo 3d5 / 2 (230.25 eV) of Mo(VI). According to the two groups of peak areas, tetravalent Mo is the main component, while Mo6 + This is mainly due to the fact that ammonium molybdate tetrahydrate did not fully participate in the reaction. Figure 2 In the S2p spectrum of c in the figure, two obvious peaks at 163.17 and 161.92 eV of a-MoS2 / DT@CNTs were observed, pointing to S2p1 / 2 and S2p3 / 2, respectively. Figure 2 The positions of the S2p1 / 2 (163.29) and S2p3 / 2 (161.94 eV) peaks in the d a-MoS2 are lowered, indicating that the addition of DT leads to a decrease in the chemical bond energy within the amorphous MoS2 molecule, and the energy required in the redox process is lower, making Na + The insertion and removal are easier to carry out, Figure 2 Corresponding to the c Raman result in .

[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing an amorphous molybdenum disulfide nanocomposite material, characterized in that: The steps include: S1. Add CNTs into deionized water and stir to obtain a CNTs solution; S2. Add (NH4)6Mo7O to the CNTs solution in S1. 24 4H2O, C2H5NS and C8H4Na2O4, stir for 10-50min to form a mixed solution; S3, transferring the mixed solution in S2 to a 100 mL polytetrafluoroethylene-lined autoclave for reaction to obtain a black product; S4, collecting the black product described in S3, and washing it three times with deionized water and anhydrous ethanol respectively; S5, placing the washed black product in an oven to dry, to obtain an a-MoS2 / DT@CNTs composite material; The reaction temperature in S3 is 90-240° C., and the reaction time is 0.5-5 h.

2. The method for preparing an amorphous molybdenum disulfide nanocomposite material according to claim 1, characterized in that: The CNTs in S1 are one or two of graphene, single-walled carbon nanotubes, and double-walled carbon nanotubes.

3. The method for preparing an amorphous molybdenum disulfide nanocomposite material according to claim 1, characterized in that: The stirring time in S1 is 10-50 min.

4. The method for preparing an amorphous molybdenum disulfide nanocomposite material according to claim 1, characterized in that: (NH4)6Mo7O in S2 24 The molar ratio of 4H2O, C2H5NS and C8H4Na2O4 is 1:1:0.05-1:20:0.

5.

5. The method for preparing an amorphous molybdenum disulfide nanocomposite material according to claim 1, characterized in that: In S5, the washed black product is placed in an oven at 60-80°C and dried for 12-24 hours.

6. The amorphous molybdenum disulfide nanocomposite material prepared by the preparation method according to any one of claims 1 to 5.

7. The amorphous molybdenum disulfide nanocomposite material prepared by the preparation method according to any one of claims 1 to 5 or the amorphous molybdenum disulfide nanocomposite material according to claim 6 in the preparation of MoS x Application in sodium battery negative electrode materials.

8. A method for MoS x A negative electrode material for a sodium battery, characterized in that: The negative electrode material contains the amorphous molybdenum disulfide nanocomposite material according to claim 6.

Citation Information

Patent Citations

  • MoS2 / GNRs composite material with loose three-dimensional winding structure, preparation method and application thereof

    CN107394184A

  • Double-carbon composite molybdenum sulfide composite material for sodium-ion battery negative electrode material and preparation method

    CN111276679A